Umetni kolčni sklepi kovina/kovina - Milošev, Ingrid (Vakuumist, 2001)
Total hip replacements (THR) which have been used in the last three decades in orthopaedics are made almost exclusively from metal femoral stem and polyethylene acetabular cup. The lifetime of THR is affected by a number of factors among which the most important is the process of aseptic loosening. It is primarily related to the wear of polyethylene cup. In order to avoid such a wear process today there is a revival of intrest in THR desings including metal femoral stems and metal cup. In the paper some main characteristics of these implants are discussed.
Keywords: ortopedija; kolčni sklep; kolki; zlitine; obraba